Convergence of infectious and non-communicable disease epidemics in rural South Africa: a cross-sectional, population-based multimorbidity study - Emily B Wong, MD; Stephen Olivier, MA; Resign Gunda, PhD; Olivier Koole, PhD; Ashmika Surujdeen, BSc; Dickman Gareta, MSc; Day Munatsi, MBA; Tshwaraganang H Modise, MSc; Jaco Dreyer, NDipIT; Siyabonga Nxumalo, BSc; Theresa K Smit, PhD; Greg Ording-Jespersen, NDipIT; et al. (Elsevier, 2021)
Summary: Background: There has been remarkable progress in the treatment of HIV throughout sub-Saharan Africa, but there are few data on the prevalence and overlap of other significant causes of disease in HIV endemic populations. Our aim was to identify the prevalence and overlap of infectious and non-communicable diseases in such a population in rural South Africa. Methods: We did a cross-sectional study of eligible adolescents and adults from the Africa Health Research Institute demographic surveillance area in the uMkhanyakude district of KwaZulu-Natal, South Africa. The participants, who were 15 years or older, were invited to participate at a mobile health camp. Medical history for HIV, tuberculosis, hypertension, and diabetes was established through a questionnaire. Blood pressure measurements, chest x-rays, and tests of blood and sputum were taken to estimate the population prevalence and geospatial distribution of HIV, active and lifetime tuberculosis, elevated blood glucose, elevated blood pressure, and combinations of these. Findings: 17 118 adolescents and adults were recruited from May 25, 2018, to Nov 28, 2019, and assessed. Overall, 52·1% (95% CI 51·3-52·9) had at least one active disease. 34·2% (33·5-34·9) had HIV, 1·4% (1·2-1·6) had active tuberculosis, 21·8% (21·2-22·4) had lifetime tuberculosis, 8·5% (8·1-8·9) had elevated blood glucose, and 23·0% (22·4-23·6) had elevated blood pressure. Appropriate treatment and optimal disease control was highest for HIV (78·1%), and lower for elevated blood pressure (42·5%), active tuberculosis (29·6%), and elevated blood glucose (7·1%). Disease prevalence differed notably by sex, across age groups, and geospatially: men had a higher prevalence of active and lifetime tuberculosis, whereas women had a substantially high prevalence of HIV at 30-49 years and an increasing prevalence of multiple and poorly controlled non-communicable diseases when older than 50 years. Interpretation: We found a convergence of infectious and non-communicable disease epidemics in a rural South African population, with HIV well treated relative to all other diseases, but tuberculosis, elevated blood glucose, and elevated blood pressure poorly diagnosed and treated. A public health response that expands the successes of the HIV testing and treatment programme to provide multidisease care targeted to specific populations is required to optimise health in such settings in sub-Saharan Africa. Funding: Wellcome Trust, Bill & Melinda Gates Foundation, the South African Department of Science and Innovation, South African Medical Research Council, and South African Population Research Infrastructure Network. Translation: For the isiZulu translation of the abstract see Supplementary Materials section.